Bringing efficiencies to tens of thousands of journals: The role of Open Source (PUBMET, 2022)
In addition to the growing number of scholarly journals published by the so-called “big five”, there are tens of thousands of journals that are published by individual scholars or by academic institutions. These smaller operations are a source of great bibliodiversity that deserves to be encouraged but can also be seen as inefficiencies in the system as a whole. The use of a common software—Open Journal Systems (OJS)—is helping these journals take advantage of an economy of scale without needing to centralize or homogenize them. The key to promoting both efficiency and bibliodiversity is in OJS’s open source nature. This presentation will describe the ways in which PKP’s open source software is bringing efficacy to journal operations, to the discovery of their content, and, in the best of cases, to supporting a transformation of the system as a whole.